Addressing Fundamental Uncertainty in Benefit–Cost Analysis: The Case of Deep Seabed Mining. Issue 1 (10th February 2021) - Krutilla, Kerry; Good, David; Toman, Michael; Arin, Tijen
Abstract: Mineral deposits of base metals, precious metals, and rare earth elements have been discovered on deep seabeds, and the commercial exploitation of these resources seems poised to begin after faltering for many years. The development of seabed resources could be socially beneficial if all goes well, but the industry faces daunting challenges and uncertainties. Emerging regulations and contracting mechanisms are the principal means for managing these uncertainties. This article recommends a complementary approach: the use of ex ante benefit–cost analysis of proposed seabed mining contracts that incorporates a fundamental uncertainty evaluation. We argue that such an ex ante evaluation will improve the state of information for the decision-making, reducing the risk of regulatory noncompliance or costly contract disputes after seabed mining begins.